A perspectiva do espaço e os conflitos pós-modernos em Mário de Carvalho: uma leitura do romance Um deus passeando pela brisa da tarde - CARDOSO, Luan Passos (2019)
Human history is constituted by diverse conflicts that go from the conquest by a territory until the imposition of a culture or ideology. Conquering space is part of the world's own biological genesis, which causes all living beings on this planet to be naturally expansive. Although, seemingly there is room for all, humanity was educated to accept hierarchies divided into leaderships, holders of the supreme power and led, represented by the servile layer. This thought was one of the main foundations that grounded the social and ideological structures of empires, and it is under this very aspect of imperial society that the plot of the novel A god strolling in the afternoon breeze, by the Portuguese author Mário de Carvalho develops. The novel is set in a Roman city, Tarcisis, belonging to the territory of Lusitania, in the second century AD. C, commanded by magistrate Lúcio Valério Quíncio who, in addition to managing the daily conflicts, needed to solve an imminent invasion of the Moors and the emergence of a new religious sect, which sought to convince the citizens of Tarcisis to deny Roman values and convert to Christianity. Even the plot of the work being dated in the second century d. C, it is noticeable that the author wrote a memoirist novel that rescues, through fiction, ancient thoughts and feelings, but which resemble contemporary behavior, thus mirroring the social agitations of the present as like those of the past. In order to encompass such a problem, the literary analysis of this postmodern novel will be based not only on the reflections that guide Postmodernism, but - and above all - the theoretical postulates of Humanist Cultural Geography, in which conflicts of territoriality, feelings of place and crowding, place-without-place and non-place. The contributions of Bachelard, Dardel, Tuan, and Relph will serve as a theoretical contribution to Postmodernism, the studies of Bauman, Hall, Eagleton and Arnaut and, as far as Humanist Cultural Geography is concerned.